2022
DOI: 10.3389/fbioe.2022.1049894
|View full text |Cite
|
Sign up to set email alerts
|

A novel dental infiltration resin based on isosorbide-derived dimethacrylate with high biocompatibility, hydrolysis resistance, and antibacterial effect

Abstract: Objectives: The available infiltration resin has raised biosafety and treatment stability concerns because of the cytotoxicity of the main component, TEGDMA, and its susceptibility to hydrolysis in the oral environment. This study aimed to develop a TEGDMA-free infiltration resin to overcome these drawbacks.Methods: Using the synthetic bioderived monomer bis(methacrylate) isosorbide (IBM) and the zwitterionic compound 2-methacryloyloxyethyl phosphorylcholine (MPC), a novel infiltrant IBMA was developed and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…The syntheses of methacrylated alkyl 3-hydroxybutyrates were described in our previous article [46]. The DSC and TGA analyses revealed that ISDMMA is a polymerizable monomer that can be used for cross-linking applications due to the nature of its molecular structure, as reported in previously published articles [44,45]. Moreover, its heat-resistant index reaches a value appropriate in various usage fields.…”
Section: Ability Of Isosorbide Dimethacrylate To Enhance Thermo-mecha...mentioning
confidence: 65%
“…The syntheses of methacrylated alkyl 3-hydroxybutyrates were described in our previous article [46]. The DSC and TGA analyses revealed that ISDMMA is a polymerizable monomer that can be used for cross-linking applications due to the nature of its molecular structure, as reported in previously published articles [44,45]. Moreover, its heat-resistant index reaches a value appropriate in various usage fields.…”
Section: Ability Of Isosorbide Dimethacrylate To Enhance Thermo-mecha...mentioning
confidence: 65%